Conceptualizing and Measuring Service Quality: Towards Consistency and Clarity in its Application to Travel Agencies in China. Issue 4 (1st October 2016) - Chen, Hanyu; Weiler, Betty; Young, Martin; Lee, Yun Lok
ABSTRACT: This article assembles research published in Chinese-language journals and the more mainstream English-language journals to present a critical review of the literature on service quality of travel agencies in China. A brief background to travel agencies in China and a bibliometric analysis of the literature is followed by a thematic analysis of conceptual articles. Combining this with a critical analysis of empirical studies allows for identification of theoretical and practical issues, notably the ambiguity and inconsistency that is pervasive in the conceptualization, operationalization and measurement of service quality. Recommendations for future research regarding service quality of Chinese travel agencies are provided.